MEDIA DISCOURSE GENRES ORGANIZATION CRITERIA AND THEIR FUNCTIONS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
In the field of comprehensive linguistic research on media discourse, it is recommended to use a number of criteria to distinguish between genres. These criteria may include expression and standard ratio, informative and evaluative elements, contextual factors, communicative purpose, pragmatic attitude, addressee characteristics, compositional structure, communication channel and image of the author, etc.